If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x + 42 = 5x + 14 + -13x Reorder the terms: 42 + -10x = 5x + 14 + -13x Reorder the terms: 42 + -10x = 14 + 5x + -13x Combine like terms: 5x + -13x = -8x 42 + -10x = 14 + -8x Solving 42 + -10x = 14 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 42 + -10x + 8x = 14 + -8x + 8x Combine like terms: -10x + 8x = -2x 42 + -2x = 14 + -8x + 8x Combine like terms: -8x + 8x = 0 42 + -2x = 14 + 0 42 + -2x = 14 Add '-42' to each side of the equation. 42 + -42 + -2x = 14 + -42 Combine like terms: 42 + -42 = 0 0 + -2x = 14 + -42 -2x = 14 + -42 Combine like terms: 14 + -42 = -28 -2x = -28 Divide each side by '-2'. x = 14 Simplifying x = 14
| 27y^3+x^9= | | 7(5a+6)=2(3a+8) | | -11(6x-22)=6x+40 | | -3m+16-(-13m)= | | -2(t-4)+9t=3t-5 | | 20a^2-64a-21=0 | | 5.5-x=4x-1 | | (x+4)+8=(4+x)+8 | | 3x+4=35 | | 100x^4+85x^3-97x^2-28x=0 | | -6v-16=8(6v-2) | | A=z+znf | | 2x-13y=-5 | | 3-4(x+5)=7x-17 | | 7(3a+6)=2(3a+8) | | 8n-40=-4(-5n+1) | | 8n-40=-4n(-5n+1) | | 30=6-4n | | 9x-3y=-9 | | 7(w-4)=6(9+w) | | 3(8-6k)=2+4k | | 2(2p+5)-27=x | | 3s^2+16s+21=0 | | 4x-4=3x+7 | | 2(x-9)+x=3(x-8)+6 | | 4x+2y=22 | | 5x-7=5(x-1) | | 4(x+4)=3x | | 4(x+4)=3x | | 9a^2-100=0 | | 4+t=32 | | 2(2p+5)-27= |